Sensitivity and Accumulation of Perfluorooctanesulfonate and Perfluorohexanesulfonic Acid in Fathead Minnows (Pimephales promelas) Exposed over Critical Life Stages of Reproduction and Development. (29th January 2021) - Suski, J.G.; Salice, C.J.; Chanov, M.K.; Ayers, J.; Rewerts, J.; Field, J.
Abstract: Per‐ and polyfluoroalkyl substances (PFAS) have emerged as contaminants of environmental concern following release from industrial practices and use of aqueous film–forming foam (AFFF). Of the identified PFAS in surface water samples from known AFFF release sites, perfluorooctanesulfonate (PFOS) and perfluorohexanesulfonic acid (PFHxS) are frequently detected. The focus of the present study was to determine the effects of PFOS and PFHxS to the native (and common) fathead minnow, Pimephales promelas, over critical life stages of reproduction and development. Two separate, 42‐d experiments were carried out using sexually mature fish, exposed to either PFOS or PFHxS. Measured exposure concentrations for PFOS and PFHxS were 0, 44, 88, 140, and 231 µg/L and 0, 150, 300, 600, and 1200 µg/L, respectively. At day 21 of the adult exposure, eggs were collected and reared for 21 d to determine the effects of PFOS or PFHxS on development, growth, and survival of larvae. The no‐observable‐effect concentration (NOEC) for PFOS was 44 µg/L, and the lowest‐observable‐effect concentration was 88 µg/L based on reduced growth in juvenile (F1) fish. Effects from PFOS exposures that did not follow a standard dose–response curve were reduced gonadosomatic index in adult males (at 44 µg/L) and reduced fecundity in females (at 140 µg/L). There was no toxicity on apical endpoints to report on adult or juvenile fish exposed to PFHxS up to 1200 µg/L. Importantly, we note that both PFOS and PFHxS accumulated in gonads and liver of adult fish following the respective exposures. The present study supports previous literature on PFOS toxicity and accumulation in fathead minnows but resulted in a lower NOEC than previously established for this species. Environ Toxicol Chem 2021;40:811–819. © 2020 SETAC